REFLECTION ON ISLAMIC EDUCATION TEACHER PRACTICE: THE KEY TO CONTINUOUS PROFESSIONAL DEVELOPMENT - Rafi Saifullah; Deri Hermawan; Fadriati Fadriati; Ermis Suryana (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The rapid transformation of educational paradigms in the 21st century demands that teachers continuously improve their pedagogical, ethical, and spiritual competencies. In this context, reflection is not only a pedagogical tool but also a spiritual-moral process that aligns professional growth with Islamic values. The method used in this study is a library research method, this study synthesizes theoretical and empirical literature published between 2015 and 2024 from reputable international and national databases. The data were analyzed through qualitative content analysis using the Miles and Huberman analytical cycle to identify thematic relationships between reflective practice, teacher professionalism, and Islamic educational philosophy. The results of this study indicate that systematic reflection enhances pedagogical innovation, ethical awareness, and an institutional learning culture. Furthermore, reflective practice rooted in muhasabah and muraqabah fosters teachers' moral accountability and faith-based integrity, positioning reflection as an intellectual discipline and spiritual devotion. Challenges identified include limited institutional support, lack of reflective training, and inadequate integration of reflective culture in teacher education programs. This study concludes that reflective practice should be institutionalized as a continuous process of professional renewal and moral improvement for Islamic Education teachers, supporting the objectives of the Independent Learning policy and contributing to the development of teachers who are pedagogically competent, ethically grounded, and spiritually aware.